Investigation of Surface Properties of Fluorocarbon Films Produced Using Plasma Techniques - Jung, Se-Bi; Cho, Youn-Jeong; Lee, Jihye; Lee, Kang-Bong; Lee, Yeonhee (AMER SCIENTIFIC PUBLISHERS, 2018)
Different fluorocarbon thin films were deposited on Si substrates using two different plasma polymerization methods. Fluorine-containing hydrophobic thin films were obtained using inductively coupled plasma (ICP) and capacitively coupled plasma (CCP) with a mixture of fluorocarbon precursors (C2F6, C3F8, or c-C4F8) and an unsaturated hydrocarbon (C2H2). Different process parameters for plasma polymerization (e.g., processing time) were used to generate various fluorocarbon thin films. The hydrophobic properties and mechanical properties of the new products were measured using a profilometer, water contact angle measurements, pencil hardness, and a 90 degrees peel test. The chemical compositions of the fluorocarbon thin films were characterized using X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FT-IR). The water contact angle results showed that the ICP technique provides a more hydrophobic surface compared to the CCP technique. XPS and FT-IR analyses indicated that the ICP technique generated more fluorine-related functional groups (i.e., CF-CFn, CF2, and CF3) in the surface region, while the CCP technique produced fewer fluorine-containing functional groups. However, the fluorocarbon thin films produced using the CCP technique showed greater adhesive strength than did the fluorocarbon thin films produced using the ICP technique. These results are useful to establish the optimal condition for the fabrication of fluorocarbon films and to develop the device in bio-sensing applications.
Keywords: THIN-FILMS; ADHESION ENHANCEMENT; POLYMERIZATION; POLYMERS